Production and characterization of spray-dried theophylline powders prepared from fresh milk for potential use in paediatrics - Aguiar, João P. (2018)
"This is the accepted version of the following article: Production and characterization of spray-dried theophylline powders prepared from fresh milk for potential use in paediatrics (2017). J Pharm Pharmacol, 69: 554–566, which has been published in final form at http://dx.doi.org/10.1111/jphp.12612 . This article may be used for non-commercial purposes in accordance with the Wiley Self-Archiving Policy [http://olabout.wiley.com/WileyCDA/Section/id-820227.html]."